Emerging trends in synthesis, characterization, and mechanism of action of antibody-drug and antibody-nanoparticle conjugates - Tanu Dixit; Annamraju Aswini; Harshal Nikam; Anuradha Vaidya; Selvan Ravindran (Discover Nano)
Abstract Antibody-drug conjugates (ADCs) and antibody-conjugated nanoparticles (ACNPs) are targeted therapies achieved by combining monoclonal antibodies (mAbs) with cytotoxic payloads or nanocarriers. ADCs consist of mAbs conjugated to the cytotoxic payloads via a linker, thus enabling tumor-specific delivery and reducing systemic toxicity. ACNPs add to this targeted therapeutic window by using nanoparticles. This conjugation promotes controlled drug release, higher drug-to-antibody ratios (DAR), and reduced off-target effects. ADCs exhibit precision in cell killing but face limitations such as antigen heterogeneity and Fc-mediated sequestration, whereas ACNPs enhance payload capacity and tumor penetration through their tunable physicochemical properties. ACNPs also facilitate multivalent binding by functionalizing multiple antibody molecules on their surface, improving target cell recognition and binding strength. Recent advancements include 14 FDA-approved ADCs and ACNPs in Phase I/II trials. A critical analysis of synthesis methods reveals that site-specific conjugation techniques enhance batch consistency, while characterization technologies, such as SEC-HPLC, LC-MS/MS, and SPR, address challenges related to DAR quantification and aggregation. Linker chemistry innovations, such as PEGylated maleimides balancing hydrophilicity and stability, are highlighted alongside emerging payloads. Despite progress, both platforms face translational hurdles: ADCs contend with manufacturing complexity and resistance mechanisms, while ACNPs require standardized in vitro models to predict in vivo behavior. This review emphasizes the significance of comparative efficacy studies and strategies for optimizing antibody density and orientation on nanoparticles. Together, these insights connect the gaps between synthesis, characterization, and therapeutic outcomes, steering the future development of targeted bioconjugates.